2018
DOI: 10.1167/iovs.17-22845
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Maintains Function of Neural Crest–Derived Ocular and Craniofacial Structures in Adult Zebrafish

Abstract: PurposeRetinoic acid (RA) is required for embryonic formation of the anterior segment of the eye and craniofacial structures. The present study further investigated the role of RA in maintaining the function of these neural crest–derived structures in adult zebrafish.MethodsMorphology and histology were analyzed by using live imaging, methylacrylate sections, and TUNEL assay. Functional analysis of vision and aqueous humor outflow were assayed with real-time imaging.ResultsBoth decreased and increased RA signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…However, much of the evidence pertains to the genetic networks responsible for ectodermal and neurectodermal patterning, and little is known about the specification of the ocular NC. Indeed, the continued requirement of NC stem cells for the maintenance of adult eyes ( Jinno et al, 2010 ; Green et al, 2015 ; Chawla et al, 2018 ) emphasizes the importance of this cell population over the vertebrate lifetime. This review will provide an update of the morphogenetic, gene regulation and signaling events controlling ocular NC migration and differentiation, with particular emphasis on the ocular anterior segment.…”
Section: Introductionmentioning
confidence: 99%
“…However, much of the evidence pertains to the genetic networks responsible for ectodermal and neurectodermal patterning, and little is known about the specification of the ocular NC. Indeed, the continued requirement of NC stem cells for the maintenance of adult eyes ( Jinno et al, 2010 ; Green et al, 2015 ; Chawla et al, 2018 ) emphasizes the importance of this cell population over the vertebrate lifetime. This review will provide an update of the morphogenetic, gene regulation and signaling events controlling ocular NC migration and differentiation, with particular emphasis on the ocular anterior segment.…”
Section: Introductionmentioning
confidence: 99%
“…Pitx2 in particular has been associated with the survival and migration of NCCs, as well as the development of the optic stalk, establishment of angiogenic privilege within the cornea, and craniofacial development (10, 11, 14, 1721). FoxC1 and pitx2 are also known to interact with one another and their expression is regulated by retinoic acid signaling (13, 22, 23). Not surprisingly, mutations in NCC regulatory genes have also been associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we showed that in neural crest-derived craniofacial and ocular tissues, there is a continued need for RA in maintaining the function and integrity of these structures (Chawla, Swain, Williams, & Bohnsack, 2018 including the cornea and iridocorneal angle, which resulted in decreased aqueous outflow from the eyes (Chawla et al, 2018). This study represents the first evidence for the tight control of RA levels to maintain the normal structure and function of the anterior segment of the adult eye.…”
Section: Fgfr1mentioning
confidence: 57%
“…Chawla, Swain, Williams, & Bohnsack, 2018). In adult zebrafish, the neural crest-derived craniofacial bones, including the jaw and frontal bone, are highly sensitive to exogenous RA and the inhibition of endogenous RA synthesis.…”
mentioning
confidence: 99%